Comparative proteomic analyses of human adipose extracellular matrices decellularized using alternative procedures. Issue 9 (25th September 2018) - Thomas‐Porch, Caasy; Li, Jie; Zanata, Fabiana; Martin, Elizabeth C.; Pashos, Nicholas; Genemaras, Kaylynn; Poche, J. Nicholas; Totaro, Nicholas P.; Bratton, Melyssa R.; Gaupp, Dina; Frazier, Trivia; Wu, Xiying; et al.
Abstract: Decellularized human adipose tissue has potential clinical utility as a processed biological scaffold for soft tissue cosmesis, grafting, and reconstruction. Adipose tissue decellularization has been accomplished using enzymatic‐, detergent‐, and/or solvent‐based methods. To examine the hypothesis that distinct decellularization processes may yield scaffolds with differing compositions, the current study employed mass spectrometry to compare the proteomes of human adipose‐derived matrices generated through three independent methods combining enzymatic‐, detergent‐, and/or solvent‐based steps. In addition to protein content, bioscaffolds were evaluated for deoxyribose nucleic acid depletion, extracellular matrix composition, and physical structure using optical density, histochemical staining, and scanning electron microscopy. Mass spectrometry based proteomic analyses identified 25 proteins (having at least two peptide sequences detected) in the scaffolds generated with an enzymatic approach, 143 with the detergent approach, and 102 with the solvent approach, as compared to 155 detected in unprocessed native human fat. Immunohistochemical detection confirmed the presence of the structural proteins actin, collagen type VI, fibrillin, laminin, and vimentin. Subsequent in vivo analysis of the predominantly enzymatic‐ and detergent‐based decellularized scaffolds following subcutaneous implantation in GFP + transgenic mice demonstrated that the matrices generated with both approaches supported the ingrowth of host‐derived adipocyte progenitors and vasculature in a time dependent manner. Together, these results determine that decellularization methods influence the protein composition of adipose tissue‐derived bioscaffolds. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A:2481–2493, 2018.